Analisis Kesalahan Berbahasa pada Buku Matematika Diskrit Berdasarkan Pedoman Umum Ejaan Bahasa Indonesia (PUEBI) - Feronika Br. Siahaan; Lenni Mariana Harahap; Lucia Lidia Sinaga; Natasya Agustina; Ika Febriana (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study aims to identify and analyze language errors in the Discrete Mathematics book, which may affect the clarity and comprehension of the presented material. The analysis focuses on capitalization, punctuation, word usage, and sentence structure. The research employs a qualitative descriptive method with a literature study approach. Data were collected through in-depth reading and recording of linguistic errors found in the book's text. The results indicate that errors such as improper capitalization, punctuation mistakes, inaccurate word choices, and ineffective sentence structures can hinder the understanding of discrete mathematics concepts. Therefore, linguistic improvements are necessary to enhance the book's effectiveness and quality as a teaching material. These revisions are also expected to increase the book’s academic credibility as a reference for students and scholars.